Community and health systems barriers and enablers to family planning and contraceptive services provision and use in Kabwe District, Zambia - Adam Silumbwe; Theresa Nkole; Margarate Nzala Munakampe; Cecilia Milford; Joanna Paula Cordero; Yolandie Kriel; Joseph Mumba Zulu; Petrus S. Steyn (BMC, 2018)
Abstract Background Unmet need for contraception results in several health challenges such as unintended pregnancies, unwanted births and unsafe abortions. Most interventions have been unable to successfully address this unmet need due to various community and health system level factors. Identifying these inhibiting and enabling factors prior to implementation of interventions forms the basis for planning efforts to increase met needs. This qualitative study was part of the formative phase of a larger research project that aimed to develop an intervention to increase met needs for contraception through community and health system participation. The specific study component reported here explores barriers and enablers to family planning and contraceptive services provision and utilisation at community and health systems levels. Methods Twelve focus group discussions were conducted with community members (n = 114) and two with healthcare providers (n = 19). Ten in-depth interviews were held with key stakeholders. The study was conducted in Kabwe district, Zambia. Interviews/discussions were translated and transcribed verbatim. Data were coded and organised using NVivo 10 (QSR international), and were analysed using thematic analysis. Results Health systems barriers include long distances to healthcare facilities, stock-outs of preferred methods, lack of policies facilitating contraceptive provision in schools, and undesirable provider attitudes. Community level barriers comprise women's experience with contraceptive side effects, myths, rumours and misconceptions, societal stigma, and negative traditional and religious beliefs. On the other hand, health systems enablers consist of political will from government to expand contraceptive services access, integration of contraceptive services, provision of couples counselling, and availability of personnel to offer basic methods mix. Functional community health system structures, community desire to delay pregnancy, and knowledge of contraceptive services are enablers at a community level. Conclusions These study findings highlight key community and health systems factors that should be considered by policy, program planners and implementers in the design and implementation of family planning and contraceptive services programmes, to ensure sustained uptake and increased met needs for contraceptive methods and services.